EFFECT OF CHEMICAL FERTILIZERS ON YIELD AND NUTRITIVE VALUE OF INTERCROPPED SORGHUM BICOLOR AND LABLAB PURPUREUS FORAGES GROWN UNDER SALINE CONDITIONS - A. O. Abusuwar; S. J. Al-Solimani (Journal of Animal and Plant Sciences, 2013)
Two field experiments were carried out during 2009-10 and 2010-11 seasons at Hada Al-Sham experimental Farm of King Abdulaziz University, Jeddah, Saudi Arabia to evaluate the effect of some chemical fertilizers on productivity and nutritive value of Sorghum bicolor Var. Panar intercropped with Lablab bean (Lablab purpureus L. Sweet) in an adverse conditions of soil and irrigation water. The chemical fertilizers applied were 50 kg/ha of urea (46%N), 50kg/ha of triple superphosphate (46% P), 50 kg/ha of KNO3, 50kg/ha of NPK (20:20:40) in additition to the control. Panar and Lablab bean were sown as a pure stand and as a mixture. Treatments were laid out in a split plot design with the fertilizer treatments in the main plots and the intercropping treatments in the subplots. Parameters measured were plant height and nutritive value for the Panar, fresh and dry yields and the Land Equivalent Ratio (LER). The chemical fertilizers had no significant effects (P≤0.05) on productivity but significantly improved forage quality in terms of CP and nutrients contents.. Intercropping of Panar and Lablab significantly (P≤0.05) increased forage productivity and improved forage quality. Lablab bean was not a good competitor as it disappeared following the first cut.
Keywords: Chemical fertilization; intercropping; Lablab bean; Sorghum forage; salinity